Anticancer Activity of Clerodendron infortunatum Linn. Extract in Swiss Albino Mice - Das, Sudipta; K. Haldar, Pallab; Pramanik, Goutam; Bala, Asis; Kar, Biswakanth (Asian Journal of Chemistry, 2010)
The methanolic extract of Clerodendron infortunatum (MECI) was evaluated for anticancer activity against Ehrlich Ascites Carcinoma (EAC) in swiss albino mice. On day 1, the extract of leaves of Clerodendron infortunatum at a dose of 250 and 500 mg/kg body (b.w.) weight was administered intraperitoneal (i.p.) route and continued for 9 consecutive days. The anticancer activity of MECI was examined by determining the mean survival time, increase of life span, tumour volume, viable tumour cell count and non viable tumour cell count in experimental animal models. The extract increased the life span of Ehrlich Ascites Carcinoma treated mice and restored the haematological parameters as compared with the Ehrlich Ascites Carcinoma bearing mice. Thus, the present study suggests that the methanolic extract of Clerodendron infortunatum showed anticancer activity in tested animal models.